Electrophoresis - Ghowsi, Kiumars (IntechOpen, 2012)
Electrophoresis is defined as the transport of electrically charged particles in a direct current electric field. Electrophoretic separation is based on differential rates of migration in the bulk of the liquid phase and is not concerned with reactions occurring at the electrodes. In the early days, electrophoresis was carried out either in free solution or in the supporting media such as paper, cellulose acetate, starch, agarose, and polyacry lamide gel. In between 1950 to 1970, an enumeration of techniques and instrumentation for Electrophoresis were developed. The present book contains few fundamentals on capillary electrophoresis and diverse application of electrophoresis in general. We hope this collection will entertain the readers who are interested in fundamental as well as applications of electrophoresis in general.